Performance, behaviour and perceptions of an open educational resource-derived interactive educational resource by online and campus university students - Erin J. Ward; Brian L. Lindshield (Association for Learning Technology, 2020)
Platforms are now becoming available to allow for incorporating interactive elements into open educational resources (OERs), but little has been published about their use and effectiveness. Students enrolled in online and on-campus sections of an intermediate human nutrition course at a public Midwestern University in the United States used an OER that was adapted to an online platform, where it included embedded videos and summative assessments (interactive educational resource). Data were collected from the learning management system, course performance, resource platform and a survey. Student course grades were positively correlated with use of the interactive educational resource and percentage of questions correctly answered. Overall survey response rate was 84/109 (77.1%). Student respondents reported higher use of the interactive educational resource and preferred it over a static PDF or hard copy. Students were most motivated to utilise the interactive educational resource by the opportunity to earn extra credit followed by desire to earn a good grade. Student respondents reported that they were satisfied with their experiences using the interactive educational resource, and with a high likelihood, would recommend future students to use it. While these findings are limited to one semester at one university, they support future research efforts into the efficacy of interactive educational resources and OER-enabled pedagogy.